2019
DOI: 10.3168/jds.2018-15620
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of fatty acid and sterol profiles for the investigation of potential milk fat adulteration

Abstract: Milk fat adulteration is a common issue in Central Asia. To assess the current situation in the commercial milk market, 17 milk samples were checked for fatty acid (FA) and sterol profiles to detect potential adulteration using multivariate analysis. Analysis of FA and sterols was performed using gas chromatography with flame ionization detection and gas chromatography with mass-spectrometric detection, respectively. Cluster analysis of FA profiles revealed 3 types of milk samples: (1) samples containing a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Various advanced techniques have been developed for milk authentication. For example, chromatographic methods combined with mass spectrometry (MS) have been used for detecting milk adulteration with nitrogen-rich compounds [14,15] and vegetable oils [16], digital imaging for milk protein determinations [17] and the detection of hydrogen peroxide in milk [18], proton transfer reaction mass spectroscopy (PTR-MS) and stable isotope ratio mass spectroscopy (IRMS) for the discrimination of organic milk [19,20] and nuclear magnetic resonance (NMR) for the nontargeted detection of multiple adulterants in milk powder [21]. Moreover, infrared spectroscopy-based techniques have become the most commonly used method for determining food authenticity, and they are considered as alternatives to reference methods [22].…”
Section: Introductionmentioning
confidence: 99%
“…Various advanced techniques have been developed for milk authentication. For example, chromatographic methods combined with mass spectrometry (MS) have been used for detecting milk adulteration with nitrogen-rich compounds [14,15] and vegetable oils [16], digital imaging for milk protein determinations [17] and the detection of hydrogen peroxide in milk [18], proton transfer reaction mass spectroscopy (PTR-MS) and stable isotope ratio mass spectroscopy (IRMS) for the discrimination of organic milk [19,20] and nuclear magnetic resonance (NMR) for the nontargeted detection of multiple adulterants in milk powder [21]. Moreover, infrared spectroscopy-based techniques have become the most commonly used method for determining food authenticity, and they are considered as alternatives to reference methods [22].…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipids were extracted twice with chloroform:methanol (2:1, v/v). The detection of FA and cholesterol (CHO) was adopted from the previous report by Nurseitova et al (2019). 19 FFA constituents were assessed by gas chromatography with an HP-88 chromatographic column (Agilent Technologies, Santa Clara, CA).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…On the other hand, any differences in the supply of fermentable carbohydrate lead to altered production of acetate in the rumen, as a precursor of mammary de novo fatty acid production. Therefore, it has been proposed that fatty acids with <16 C originated from de novo synthesis and those >16 C were preformed fatty acids taken up by the mammary gland, and 16:0 and 16:1 fatty acids come from both de novo and preformed sources (59,60). However, Dewhurst et al (61) showed that actual milk yields of C15:0 and C17:0 exceeded the duodenal flow of these fatty acids.…”
Section: Productive Performance Of the Animalsmentioning
confidence: 99%